Increased Risk of Intracranial Hemorrhage in Patients With Pregnancy-Induced Hypertension: A Nationwide Population-Based Retrospective Cohort Study. Issue 20 (May 2016) - Lin, Li-Te; Tsui, Kuan-Hao; Cheng, Jiin-Tsuey; Cheng, Jin-Shiung; Huang, Wei-Chun; Liou, Wen-Shiung; Tang, Pei-Ling
Abstract : Abstract: Pregnancy-induced hypertension (PIH) may be a major predictor of pregnancy-associated intracranial hemorrhage (ICH). However, the relationship between PIH and long-term ICH risk is unknown. The objective of the study was to determine the association between PIH and ICH and to identify the predictive risk factors. Patients with newly diagnosed PIH were recruited from the Taiwan National Health Insurance Research Database. PIH patients were divided into gestational hypertension (GH) and preeclampsia groups. The 2 groups were separately compared with matched cohorts of patients without PIH based on age and date of delivery. The occurrence of ICH was evaluated in both cohorts. The overall observational period was from January 1, 2000 to December 31, 2013. Among the 23.3 million individuals registered in the National Health Insurance Research Database, 28, 346 PIH patients, including 7390 with GH and 20, 956 with preeclampsia, were identified. The incidences of ICH were increased in both groups (incidence rate ratio [IRR] = 3.72 in the GH group, 95% confidence interval [CI] 3.63–3.81, P  < 0.0001 and IRR = 8.21 in the preeclampsia group, 95% CI 8.12–8.31, P  < 0.0001, respectively). In addition, according to the results of stratification of follow-up years, both groups were associated with a highest risk of ICH at 1 to 5 years of follow-up (IRR = 11.99, 95% CI 11.16–12.88, P  < 0.0001 and IRR = 21.83, 95% CI 21.24–22.44, P  < 0.0001, respectively). After adjusting for age, parity, severity of PIH, number of PIH occurrences, gestational age, and comorbidities in the multivariate survival analysis using Cox regression model, age ≥30 years (hazard ratio [HR] 1.99, 95% CI 1.27–3.10, P  = 0.0026), patients with preeclampsia (HR 2.18, 95% CI 1.22–3.90, P  = 0.0089), multiple PIH occurrences (HR 4.08, 95% CI 1.85–9.01, P  = 0.0005), hypertension (HR 4.51, 95% CI 1.89–10.74, P  = 0.0007), and obesity (HR 7.21, 95% CI 1.58–32.84, P  = 0.0107) were independent risk factors for the development of ICH among patients with PIH. Patients with PIH, especially those with older age, preeclampsia, and multiple PIH occurrences, may have an increased risk of developing ICH later in life.